Spatial distribution and intensity of snare poaching in the Boland region of South Africa: implications for optimising anti-poaching efforts - Kendon, Tamar A (Department of Biological Sciences, 2022)
The human population of sub-Saharan Africa is growing exponentially, increasing anthropogenic impacts on natural resources, including wildlife, both inside and outside of protected areas. The rising demand for cheap sources of protein is fuelling the harvesting of bushmeat. In South Africa, illegal wire-snares are the most popular method of bushmeat harvesting. However, snare poaching is indiscriminate and inhumane, causing the death of many non-target species and suffering by all animals captured. The impacts of snaring on an ecosystem can be devastating, yet few studies have explored wire-snare poaching trends in southern Africa or on private agricultural lands. This study used data obtained during 210 snare patrols to investigate the intensity of use and spatial distribution of wire-snares across 111 private agricultural properties in the Boland region in the Western Cape province, South Africa. I considered the influence of social and ecological attributes on property-level snare use, including punitive measure enforcement, the employment of seasonal workers, farmer residency, the use of legal lethal control measures, the number of families on the property, property size, the proportion of natural land, and primary agricultural output. I also considered the influence of anthropogenic structures and abiotic variables on snare placement across the landscape, including elevation, fine-scale land-use types, slope, ruggedness, and distance to the nearest street, river, servitude area, farm boundary, and protected area. Wire-snares were largely placed close to the ground, along game trails and fence lines, and anchored to trees and fence posts. My findings reveal that snare use was higher on properties where the farmer lived permanently on the property (P = 0.005) or the primary agricultural output was orchards (P = 0.043). Snares were more likely to be present further from a public street but within roughly 1 km, close to rivers, at an elevation of 300 to 500 m, and in patches of forest plantations, wetlands, bare ground, and natural woody vegetation. There was also a strong interaction (interaction size = 116.56) between distance to street and proximity to a protected area. The predicted snare hotspots are centred around protected areas at mid-elevation (300-500 m) but are not remote in terms of distance to a public street. It is important to use these findings to inform anti-snaring efforts as wire-snare poaching is likely to be a growing threat to local biodiversity. Future studies should use questionnaires or structured interviews in conjunction with field studies to collect data on snare use. This will help to prevent the misleading interpretation of respondent claims, avoid respondent biases and improve targeted snare removal and law enforcement actions. It will also provide insight into the local context, crucial for identifying potential local drivers of snaring, such as food security, and informing the focus of awareness campaigns.